Post-treatment to enhance the mechanical performance of printed Onyx - Jimenez-Martinez, Moises; Varela-Soriano, Julio; Carrera-Espinoza, Rafael; Coca-Gonzalez, Manuel (Frontiers in Mechanical Engineering, 2025)
Additive manufacturing has high potential to achieve a low carbon footprint because it offers the possibility of fabricating components without using manufacturing tooling. However, the mechanical properties of printed components need improvement. The flexibility of the designs generated by controlling the input of the material during filament extrusion in additive manufacturing allows the fabrication of components without tools; however, crystallization occurs because of the temperature gradient in the printed layers and the layers added during printing. Temperature governs polymer crystallization kinetics. Because the material extrusion process is non-isothermal at the welding interface, polymer crystallization kinetics and degree of crystallization are determined by the thermal history developed during manufacturing. Crystallization worsens the mechanical properties because internal forces are concentrated due to the residual stresses present during cooling. There is a wide range of literature and research on the effect of post-heat treatment on improving mechanical properties in metals. To the best of our knowledge, studies on the post-processing of 3D-printed polymers are limited. This research proposes post-processing to homogenize the structure of the printed component through thermal treatment to improve the ultimate tensile strength of Onyx. Annealing and normalizing treatments almost doubled the mechanical strength of raw printed Onyx.